Overview of Fibre Optic Sensing Technology in the Field of Physical Ocean Observation - Wang, Li; Wang, Yong jie; Song, Sanming; Li, Fang (Frontiers in Physics, 2021)
Fiber optic sensors are expected to be an auxiliary measurement tool in the field of ocean observation due to their small size, easy networking, intrinsic immunity to electromagnetic interference, and many other advantages. In recent years, the research around fiber optic sensing technology in the field of physical ocean observation has received increasing attention from researchers. According to the different measurement objects and measurement principles, the focus is on the seawater temperature sensor based on fiber grating, seawater salinity sensor, seawater pressure sensor, seawater salinity sensor based on multi-core optical fiber, seawater salinity sensor based on Michelson and Mach-Zehnder interferometry, seawater pressure sensor based on Fabry-Perot cavity, fiber optic temperature salinity and depth sensors based on resonant and coupling technology, flow velocity sensor based on multi-core optical fiber and fiber optic turbulence sensors based on thermal dissipation and turbulent kinetic energy dissipation. The test methods and test results of various sensors are analyzed, and the advantages and disadvantages of the technologies are pointed out. Prospects for the application of fiber optic sensors in physical ocean observation are presented.